(untitled) (Weinheim,Chichester, 2013)
Approaching sustainability from the perspectives of engineering and multiple scientific disciplines, this book incorporates the concepts of intergenerational equity and ecological capabilities, while promoting scientific rigor for the analysis of sustainability and the use of appropriate metrics to determine the comparative merits of alternatives.
Keywords: Chemical engineering,Kỹ thuật hóa học; Environmental aspects,Khía cạnh môi trường